Managing Oaks to Produce Food for Wildlife - Holly K. Ober; Patrick J. Minogue (EDIS)
WEC-249, a 5-page illustrated fact sheet by Holly K. Ober and Patrick J. Minogue, describes the reasons homeowners should consider planting oaks, how to select the right oak species for a given site, and how to improve wildlife habitat in established stands. Includes sources of additional information. Published by the UF Department of Wildlife Ecology and Conservation, August 2008.